Pandemic response and international law: The case of COVID-19 - Qian Qin; Tianyu Luo (World Scientific Publishing, 2020)
The coronavirus pandemic is currently raging throughout the world. The ensuing crisis has acquired a multidimensional nature, affecting all levels of society, including international health legal order. For international health law, the World Health Organization (WHO) is the international institution with a core mandate in issues of global health. Moreover, the International Health Regulations (IHR) is the main legally binding instrument laying down rules for the cross-border spread of contagious diseases. Against this backdrop, this paper evaluates the issues and disputes under the current regimes of international health law. The paper then offers some thoughts by way of answers to the research questions.